2016
DOI: 10.18821/0507-4088-2016-61-2-74-78
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus infection and spontaneous abortion in pregnant women of I and II trimester

Abstract: The goal of this work was the evaluation of the frequency of human CMV infection among the women, whose pregnancy ended in miscarriage, detection of active forms of infection and treatment before pregnancy. Virological and sero-immunological techniques were used. A total of 116 women who had miscarriages before the 28 week of pregnancy were submitted to the CMV test. 109 women (94.0%) demonstrated positive results. 49 women (42.2%) had active form of the cytomegalovirus infection. 13 women (26.5%) had the recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Baghel and Inamdar (2020) found that 56% of women diagnosed with increased levels of IgG antibodies for CMV are at higher risk of pregnancy (18). In another study conducted among 116 women with previous miscarriages, the seroprevalence of all types of CMV infection increased (19).…”
Section: Discussionmentioning
confidence: 98%
“…Baghel and Inamdar (2020) found that 56% of women diagnosed with increased levels of IgG antibodies for CMV are at higher risk of pregnancy (18). In another study conducted among 116 women with previous miscarriages, the seroprevalence of all types of CMV infection increased (19).…”
Section: Discussionmentioning
confidence: 98%